Testing the efficacy of a narrative short film in educating the public about providing emotional support to individuals with fertility problems - Maija J. Kiviharju; Sarah K. Gulash; Ashley A. Balsom; Jennifer L. Gordon (Journal of Psychosomatic Obstetrics and Gynecology)
Background To educate the public on how best to support people with fertility problems, a narrative short film “Ten Things Not to Say to Someone Struggling with Infertility” was created, depicting the impact that helpful versus unhelpful dialogue has on someone with fertility problems.Methods Before and after watching the video, 419 participants from the public were presented with a hypothetical vignette describing a woman experiencing fertility problems and asked about the likelihood that they would endorse a series of helpful and unhelpful statements when communicating with the protagonist. Pre and post endorsement of helpful versus unhelpful statements were compared, as were self-perceived knowledge about the mental health aspects of fertility problems, confidence in providing emotional support to someone with fertility problems, and empathy for the protagonist.Results Participants endorsed fewer unhelpful statements after the video relative to before (M(SD) = 2.2(2.3) vs. 1.3(2.3), p < .001) and fewer participants endorsed at least one unhelpful statement (72% to 47%, p < .001). Self-perceived knowledge of fertility problems, confidence in providing support, and empathy increased at post-test (ps < .001; Cohen’s d = .56–.83) indicating medium-large effects.Conclusions A narrative short film appears to be an effective dissemination strategy for sensitizing the public to the emotional struggles of individuals experiencing fertility problems.